Avaliação da distância de dispersão de sementes de uma espécie de planta da Mata Atlântica: uma comparação entre primatas e aves - Garcia, Giuliana [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Seed dispersal helps maintaining gene flow between individuals of plants species, therefore, the activity of frugivorous dispersers partially determines the spatial distribution of plants. The loss of dispersers can reduce seed dispersal distances, aggregating the population, which can reduce gene flow and increase the likelihood of developing a genetic structure. Thus the occurrence of inbreeding can increase, weakening populations and exposing them to the possibility of local extinction. In this project we studied the fine-scale spatial genetic structure of adults of a rain forest tree species. Cryptocarya mandioccana (Lauraceae) and the seed dispersal distance by two dispersers od Ilha do Cardoso State Park: the guariba (Primates: Atelidae) and the Aburria jacutinga (Aves: Cracidae). The evaluation of seed dispersal distances can help characterizing the role of animal species in the gene flow and the spatial distribution of plant species, which allows predicting the possible effects of their local extinctions. The source tree of defecated seeds was determined comparing 106 adult tree genotypes of C. mandioccana with the genotype of 81 mother origin tissue of seeds. In order to perform this, we utilized 6 microsatellite loci specific for C.mandioccana and the kinship analyses to determine the source tree. We found high genetic diversity in adult population (A=9,33; He=0,73; Ho= 0,57). The adult trees of C. mandioccana didn't show, for major distance classes, significative fine-scale spatial genetic structure. We also observed a high variability of seeds genotypes, only three of them dispersed by howler monkey or Black-fronted Piping-Guan and therefore was calculated the distance between them and the maternal-tree. Throughout the genotype analyses of seeds found in fezes, we estimated the approximated number adults that could have possible originated them. We noticed that seeds dispersed by howler-monkeys have a higher diversity...

A dispersão de sementes atua mantendo o fluxo gênico entre os indivíduos das espécies de plantas, portanto, a atividade dos frugívoros dispersores determina parcialmente a distribuição espacial destas. A perda dos dispersores pode reduzir a distância a que estes dispersam, agregando as populações, o que pode reduzir o fluxo gênico e aumentar a probabilidade de desenvolver uma estrutura genética. Com isso a ocorrência de endocruzamento pode aumentar, debilitando as populações e expondo-as à possibilidade de uma extinção local. Neste projeto, foi estudada a estrutura genética espacial de adultos de uma espécie de árvore da Mata Atlântica, Cryptocarya mandioccana (Lauraceae), e a distância de dispersão das sementes pelos dois dispersores presentes no Parque Estadual Ilha do Cardoso (SP): o Alouatta guariba (Primates: Atelidae) e a Aburria jacutinga (Aves: Cracidae). A avaliação da distância de dispersão pode ajudar na caracterização do papel das espécies animais no fluxo gênico e na distribuição espacial das espécies de plantas, o que permite prever os possíveis efeitos de suas extinções locais. Determinamos a árvore-mãe das sementes defecadas comparando o genótipo de 106 árvores adultas de C. mandioccana com o tecido de origem materna de 81 sementes. Para isso, utilizamos 6 lócus microssatélites específicos à C. mandioccana e a análise de parentesco para determinar a árvore de origem. Foram encontrados altos níveis de diversidade genética na população de adultos (A=9,33; He=0,73; Ho= 0,57). As árvores adultas de C. mandioccana não mostraram na maioria das classes de distância estrutura genética espacial significativa. Também observamos uma alta variabilidade de genótipos entre as sementes, somente três destas dispersas por bugio e jacutinga corresponderam ao genótipo de adultos e, portanto, foi traçada a distância a que estas foram dispersas em relação a arvore-mãe. Através da...
Keywords: Sementes; Sementes - Disseminação; Animais frugivoros; Sementes - Distribuição geográfica; Genetica molecular; Cardoso, Ilha do (SP); Mata Atlântica